Understanding of mass transfer resistance for the adsorption of solute onto porous material from the modified mass transfer factor models - Fulazzaky, Mohamad Ali; Khamidun, Mohd Hairul; Omar, Roslan (Elsevier, 2013)
Mass transfer is important in separation and is essential for adsorption process. Mass transfer resistance controls the adsorption kinetic rate, but there is only limited understanding of the adsorption of a solute onto porous material from surface water. This study investigates the adsorptions of NHþ 4 and Al3+ onto granular activated carbon from surface water using the laboratory-scale plug flow column. The use of the modified mass transfer models is able to determine the resistance of mass transfer for the adsorption of one or more solutes present in surface water onto porous material. In this case study identified that the resistance of mass transfer is dependent on film mass transfer before and porous diffusion after break- through occurred. The research findings advance understanding of novel approach for investigating mass transfer resistance of solute onto porous material from waters.